Cross-Cultural Trends in the Development of Contemporary Illustration Design - Lao, Ji (Art and Society, 2026)
Illustration design has evolved, moving beyond traditional drawing to emphasize decoration, flexibility, and diverse elements. It serves as a key information medium, expressing emotions and inner desires. Integrating high-tech and traditional forms, contemporary cutting-edge illustration is subversive, catering to modern consumption needs. Blending traditional Chinese essence with modern visuals, it boasts urban vitality and aesthetic appeal, driving innovation in Chinese and global illustration.